2015
DOI: 10.7554/elife.08973
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional interactions between indomethacin and the murine intestinal microbiota

Abstract: The vertebrate gut microbiota have been implicated in the metabolism of xenobiotic compounds, motivating studies of microbe-driven metabolism of clinically important drugs. Here, we studied interactions between the microbiota and indomethacin, a nonsteroidal anti-inflammatory drug (NSAID) that inhibits cyclooxygenases (COX) -1 and -2. Indomethacin was tested in both acute and chronic exposure models in mice at clinically relevant doses, which suppressed production of COX-1- and COX-2-derived prostaglandins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 91 publications
4
67
0
1
Order By: Relevance
“…Though a previous study showed a different gut microbial alteration after indomethacin treatment in mice14, the present study differs by employing 16S rRNA sequencing on serial samples from the same mouse, reducing individual variations to visualize the gut microbial alteration. And these compositional changes in microbiota are consistent with another sequencing study15.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though a previous study showed a different gut microbial alteration after indomethacin treatment in mice14, the present study differs by employing 16S rRNA sequencing on serial samples from the same mouse, reducing individual variations to visualize the gut microbial alteration. And these compositional changes in microbiota are consistent with another sequencing study15.…”
Section: Discussionsupporting
confidence: 90%
“…The composition after this adaptive change is significantly different from the original commensals; nevertheless, we also acknowledge that our experiments have not provided mechanistic insights to small bowel enteropathy. In a recent study, antibiotic pretreatment was shown to reduce gut de-glucuronidation and result in increased indomethacin elimination, therefore preventing the mucosae from injury15. Antibiotic pretreatment may affect the pathogenesis through altering the drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between mice and rats may in part be related to the absence of a gall bladder in rats, but obviously, other species-related differences may play a role. A recent study reported on the acute and chronic effects of indomethacin supplementation in BL6 mice based on 16S ribosomal RNA (rRNA) gene amplicon sequencing [38]. Using an acute dose about 10 times higher than the dosage used in the present experiments, the authors found that the abundance of Peptococcaceae in the fecal samples increased already after 6 h. Exposure for 7 days using a dosage similar to the one used here resulted in no significant changes in the fecal microbiome, whereas an increased abundance of Peptococcaceas was observed in samples from cecum and the large intestine [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported on the acute and chronic effects of indomethacin supplementation in BL6 mice based on 16S ribosomal RNA (rRNA) gene amplicon sequencing [38]. Using an acute dose about 10 times higher than the dosage used in the present experiments, the authors found that the abundance of Peptococcaceae in the fecal samples increased already after 6 h. Exposure for 7 days using a dosage similar to the one used here resulted in no significant changes in the fecal microbiome, whereas an increased abundance of Peptococcaceas was observed in samples from cecum and the large intestine [38]. This finding and the clear effects of the microbiota on the metabolism of indomethacin suggest that some of the strain-specific effects of indomethacin supplementation may relate to differences in composition of the microbiota and changes in the gut not reflected in fecal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these types of effects occur following treatment with other NSAIDs or chemopreventive agents with different mechanisms of action should be evaluated. In fact, recently published work by Liang et al ., provides some evidence for this concept by demonstrating that administration of indomethacin to mice induces a shift in the luminal microbiota with a reciprocal effect of the bacteria on drug metabolism (34). Taking into consideration the Liang study as well as the current work, it is possible that several NSAIDs may exert effects on the luminal microbiota, which could explain in part, the chemopreventive efficacy of this class of compounds.…”
Section: Discussionmentioning
confidence: 99%